2020
DOI: 10.1007/s40745-020-00307-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Confidence Interval for a Univariate Stock Price Signal Predicted Through Long Short Term Memory Network

Abstract: In this paper, we show an innovative way to construct bootstrap confidence interval of a signal estimated based on a univariate LSTM model. We take three different types of bootstrap methods for dependent set up. We prescribe some useful suggestions to select the optimal block length while performing the bootstrapping of the sample. We also propose a benchmark to compare the confidence interval measured through different bootstrap strategies. We illustrate the experimental results through some stock price data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Azlan et al [3] conducted a time series analysis using the clonal selection algorithm and found almost similar forecasting performance as ARIMA models on yahoo stock price. In time series forecasting, LSTM models illustrated superior forecasting performance with a long-term confident band [4]. Li and Bastos [26] conducted a systematic literature review that reported LSTM is the most widely used deep learning technique on stock price forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Azlan et al [3] conducted a time series analysis using the clonal selection algorithm and found almost similar forecasting performance as ARIMA models on yahoo stock price. In time series forecasting, LSTM models illustrated superior forecasting performance with a long-term confident band [4]. Li and Bastos [26] conducted a systematic literature review that reported LSTM is the most widely used deep learning technique on stock price forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 1 illustrates the overall structure of our experiment design based on Alinma dataset and then we replicate the same procedure for the other selected datasets. A sliding window of size five is commonly used in forecasting stock price, mentioned in the surveyed literature [3], [4], [8]. As a result, the feature list contains stock prices of t-4, t-3, t-2, t-1, t days where t corresponds to today.…”
Section: Experiments Designmentioning
confidence: 99%